Prevention Is the Best Intervention: Proactive Strategies for Supporting Students Who Engage in Escalated Behaviors. (December 2022) - Robinson, Jason; Duncan, Kristin; London, Dina; Gershwin, Tracy; Trapp, Laura; Shen, Guofeng
Strategies for preventing the escalation of problematic student behavior in inclusive school settings are detailed. These strategies include utilizing proactive behavioral interventions, implementing function-based behavioral interventions that address root causes of escalated student behaviors, and teaching and reinforcing socially acceptable alternatives to escalated student behaviors. Each strategy is described in practical detail using case study vignettes about students who engage in escalated behaviors within inclusive school settings.